Weird Tales Volume 1 - Hoffmann, E.T.A. (Saga Egmont, 2022)
‘Weird Tales Volume 1’ (1885) was written by German Romantic author E. T. A. Hoffmann, most famous for his novella ‘The Nutcracker and the Mouse King’ (1816). Included in this first of two volumes are the short stories: The Cremona Violin, The Fermata, Signor Formica, The Sandman, The Entail and Arthur’s Hall. These classic short stories are perfect for fans of horror and fantasy fiction and the authors H. P. Lovecraft and Neil Gaiman. Ernst Theodor Wilhelm Hoffmann (1776-1822), better known as E. T. A. Hoffmann, was a German Romantic author of fantasy and gothic horror. He was also a composer, music critic, draftsman and caricaturist. Hoffmann\'s stories inspired several famous operatic composers including Richard Wagner, Jacques Offenbach and Léo Delibes. He is also the author of the novella ‘The Nutcracker and the Mouse King’, on which Tchaikovsky’s famous ballet, ‘The Nutcracker’ is based. The story also inspired the film ‘The Nutcracker and the Four Realms’ (2018), starring Keira Knightley, Morgan Freeman, Helen Mirren.